Performance Prediction Model on Driving Train Simulator Based on Alertness and Sleepiness Level Result - Ayu Pramiarsih; Daniel Siswanto; Sani Susanto (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2021)
alertness and sleepiness level. Fatigue is also caused by boredom due to monotonous road conditions. One way to prevent accidents is to predict one's driving performance when carrying out their duties. This study aims to build a performance prediction model based on the results of the level of alertness and sleepiness test in monotonous road conditions. This study uses a Train Simulator for 120 minutes to describe a driving activity. This study involved 5 male and 3 female participants aged 22-38 years. Each participant will receive the same treatment based on sleep duration (4 and 8 hours) and sleep quality (good and poor) the night before. Performance prediction models are built using multiple regression analysis based on the highest adjusted coefficient of determination (R2). The results of a performance prediction model with an adjusted R2 of 61.2% and with the final variable entered into the model based on Psychomotor Vigilance Test (PVT) measurement tools is mean reaction time (MRTPVT), Sustained Attention Test (SAT) measurement tools are % number of missed targets (NMTSAT), and SOFI measurement tools are physical exertion (PE).